Letter from Patterson Du Bois to Margaret M. Booth, October 11, 1888 - Du Bois, Patterson (1888)
Patterson Du Bois writes to Margaret M. Booth née Cardeza to inform her that 50 printed copies of Du Bois' memorial to her late husband have been ordered for her.
Keywords: Booth, James Curtis, 1810-1888; Martinez Cardeza, Margaret